2004
DOI: 10.1080/03014223.2004.9518374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concentration of anal gland scent lures on the capture rate of ferrets (Mustela furo) in winter and spring

Abstract: We tested scent lures made from the anal gland secretions of male and female ferrets (Mustela furo L.) at 0.1-2% concentration in "Albert", a solid, long-life, casein-based formulation, as attractants for feral ferrets in winter and spring. Live traps at 10 study sites in Canterbury and Otago lured with 2% female scent caught significantly more ferrets (1.00 per 100 corrected trap nights) than those lured with a fish-based paste (0 per 100 CTN), and at least twice as many as those lured with male scent or lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Secretions were extracted using a needle and syringe inserted through the wall of the anal sac, mixed in vegetable oil and diluted to make a 1% solution. Previous studies have demonstrated detectability of, or attraction to, anal gland secretions at dilutions comparable to this, and lower, by ferrets (Woodley & Baum 2003;Spurr et al 2004) and stoats (Clapperton et al 1999). Secretions of each species appeared different in colour, consistency and odour, and the odour of the diluted solution was detectable to humans at a distance of approx.…”
Section: Odour Preparationmentioning
confidence: 73%
“…Secretions were extracted using a needle and syringe inserted through the wall of the anal sac, mixed in vegetable oil and diluted to make a 1% solution. Previous studies have demonstrated detectability of, or attraction to, anal gland secretions at dilutions comparable to this, and lower, by ferrets (Woodley & Baum 2003;Spurr et al 2004) and stoats (Clapperton et al 1999). Secretions of each species appeared different in colour, consistency and odour, and the odour of the diluted solution was detectable to humans at a distance of approx.…”
Section: Odour Preparationmentioning
confidence: 73%
“…Stimuli are based on the 4F motivations of animal behaviour: food (energy demands), fornication (mating and other social interactions), fight (competition), and fear (predator avoidance). Individual variability will influence behavioural responses; for example, a stimulus that deters most individuals may attract others (e.g., aggressive conspecific vocalisation) or the rate of habituation can relate to an animal's personality [25,[71][72][73][74][75][76][77][78][79][80][81].…”
Section: How Can We Strategically Manage the Challenges And Opportunities Of Habituation To Devices?mentioning
confidence: 99%
“…Each Scentinel in this trial was equipped with a Ferret-specific lure containing a 2% extract of female Ferret anal gland in a 3.5 g block of 'Albert' slow-release matrix. In previous experiments (Spurr et al . 2004), this formulation gave a significant increase in capture rate of Ferrets of both sexes.…”
Section: T H E S C E N T I N E L a U T O M A T E D M O N I T O Rmentioning
confidence: 85%